Internalisasi Nilai-Nilai Sosial Shalat dalam Pembelajaran untuk Penguatan Karakter Peserta Didik: Sebuah Kajian Konseptual - Dudi Muharam; Yurna Bachtiar; Amirulloh Amirulloh; Agus Mulyadi; Arif Saipullah; ikbal fatardo (Universitas Muhammadiyah Mataram, 2026)
Education is not merely a process of transferring scientific knowledge, but a humanistic endeavor to cultivate noble character. Amidst modern advancements that frequently trigger social fragmentation and moral crises among the younger generation, strengthening students' character has become an urgent priority that cannot be delayed. Prayer (shalat), often understood solely as a vertical ritual between a servant and the Creator, inherently possesses a rich social dimension—encompassing discipline, equality, empathy, and peace. Unfortunately, this transformative potential is still frequently overlooked in Islamic Religious Education (PAI) practices in schools, where ritual worship has not fully manifested into daily social behavior.This conceptual study aims to elaborate on how the internalization of the social values of shalat can be meaningfully integrated into the learning process to strengthen the humanistic character of students. Utilizing a descriptive qualitative research method, this study profoundly examines various literatures, pedagogical concepts, and religious texts to present a comprehensive framework of ideas.The results of the study indicate that internalizing the social values of shalat in learning must touch three dimensions of humanity: cognitive awareness (knowing), emotional resonance (feeling), and behavioral habituation (acting). When PAI learning succeeds in transforming the understanding of shalat from a mere